The role of illness beliefs in understanding adjustment after stroke - Aujla, Navneet (2017)
Stroke is a highly prevalent condition. It is a principal cause of adult disability and a leading cause of death in the United Kingdom (UK). The lifetime risk of stroke recurrence is also high, particularly for those with specific risk factors (e.g., hypertension). The long-term management of stroke is multi-faceted and complex. Stroke survivors are often responsible for self-managing their secondary preventive treatment (e.g., oral medication(s)) alongside rehabilitation, which is most beneficial in the first six-months. However, patients undergo a period of psychological adjustment after stroke. This is particularly evident in the early days where mood problems, such as depression, are highly common and affect how well people engage with, and adhere to, their rehabilitation and treatment. The present PhD research was interested in further understanding adjustment after stroke, and in particular, by utilising key evidence from the field of Health Psychology (more specifically, the Common Sense Model (CSM)), examining whether survivors’ perceptions (or beliefs) about their stroke are influential in determining how well people recover.